2011
DOI: 10.1002/ejic.201000552
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Molecular Structure, and Physical Properties of the Complexes [{PhB(pz)2(CH2SMe)}2M] (M = MnII, FeII; pz = pyrazol‐1‐yl) Containing a Novel [N,N,S]‐Heteroscorpionate Ligand

Abstract: -have been synthesized and characterized by Xray crystallography, magnetic measurements, cyclic voltammetry, and various spectroscopic techniques. In the solid state, both complexes 2 and 3 possess a distorted octahedral ligand sphere, but adopt different configurations (2: cis; 3: trans). According to X-ray diffraction data, Mössbauer spectroscopy, and SQUID measurements, compound 2 exists as low-spin complex in the solid state at temperatures T Յ 20°C (μ eff ≈ 0.5 μ B ). Upon heating, the magnetic moment μ e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 69 publications
(72 reference statements)
1
9
0
Order By: Relevance
“…The average Fe-N bond length of 1.990 Å and Fe-S bond length of 2.264 Å in C1 (@173 K) are in accordance with those reported in literature and account for an iron(II) ion in the [LS] state [23][24][25][26][27][28][29]. Figure S7 shows the crystal structure/asymmetric unit of C1 (@173 K).…”
Section: Crystal Structuressupporting
confidence: 85%
“…The average Fe-N bond length of 1.990 Å and Fe-S bond length of 2.264 Å in C1 (@173 K) are in accordance with those reported in literature and account for an iron(II) ion in the [LS] state [23][24][25][26][27][28][29]. Figure S7 shows the crystal structure/asymmetric unit of C1 (@173 K).…”
Section: Crystal Structuressupporting
confidence: 85%
“…Similarly, in toluene solution it undergoes only partial SCO, as monitored by NMR (203− 298 K) and by UV−vis (283−343 K) spectroscopy. 30 To summarize, five of these six examples of structurally characterized, SCO-active N 4 S 2 -coordinated iron(II) complexes are mononuclear and one is a 1D polymer. All six feature thioether S donors.…”
Section: ■ Introductionmentioning
confidence: 97%
“…Prior to those reports, Britovsek and co-workers reported that the closely related N 4 S 2 -coordinated iron­(II) complexes [Fe II ( bpte )­(MeCN) 2 ] and [Fe II ( bptPh )­(MeCN) 2 ] undergo a gradual, almost complete SCO below room temperature in acetonitrile solution . Finally, the N 4 S 2 -coordinated iron­(II) complexes [Fe II ( [9]­aneN 2 S ) 2 ]­[ClO 4 ] 2 and {[ PhB­(pz) 2 ­ (CH 2 ­ SMe) ] 2 Fe II }, by Gahan and co-workers and by Weber, Holthausen, Wagner, and co-workers, respectively, were both reported to undergo gradual, incomplete SCO. The former complex, [Fe II ( [9]­aneN 2 S ) 2 ]­[ClO 4 ] 2 , transitions between LS in the 4–150 K range and approximately 30% HS at 300 K (see Supporting Information) in the solid state and also shows temperature-dependent magnetic susceptibility in solution .…”
Section: Introductionmentioning
confidence: 99%
“…The most widely studied SCO system is iron(II) complexes where the metal centre is surrounded by six nitrogen donors, however there are fewer examples of other metal centres and geometries [13–16] . In addition to the N 6 coordination sphere, recently, it has been demonstrated that N 4 S 2 systems can produce iron(II) SCO‐active complexes, with only a handful of ligands that can provide the right ligand field for SCO to occur, [17–23] Figure 1. All the S‐based ligands contain the same thioether functional group, in combination with amine, pyridine, triazole or pyrazole nitrogen donors, and some of them contain NCE (E=S, Se or BH 3 ) co‐ligands.…”
Section: Introductionmentioning
confidence: 99%